Kepemimpinan Melayani dalam Perspektif Eklesiologi Komunio John D. Zizioulas bagi Gereja di Indonesia - Br Tarigan, Thalia Srihati (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2026)
This paper analyzes servant leadership in the perspective of John D. Zizioulas’ ecclesiology of communion as a theological proposal for churches in Indonesia. This study is a qualitative library-based research employing normative and correlative theological approaches. The analysis engages Zizioulas’ thought on communion and perichoresis and places it in dialogue with Christ’s hospitality and servant leadership within the contemporary challenges faced by Indonesian churches. The discussion shows that the ecclesiology of communion understands the church as a fellowship rooted in the relational life of the Triune God, while perichoresis provides a dialogical, participatory, and non-dominative relational paradigm for ecclesial life. Within this framework, Christ’s hospitality functions as a bridge between the church’s liturgical identity and its social praxis, whereas servant leadership becomes the practical embodiment of communion. In the Indonesian context, marked by religious and cultural plurality, social fragmentation, and pastoral challenges, this model offers a constructive direction for the church to become a community that welcomes, restores, and empowers. Therefore, this paper argues that servant leadership grounded in the ecclesiology of communion and enriched by Christ’s hospitality offers a relevant theological contribution to the renewal of the church in Indonesia.AbstrakTulisan ini menganalisis kepemimpinan melayani dalam perspektif eklesiologi komunio John D. Zizioulas sebagai tawaran teologis bagi gereja di Indonesia. Penelitian ini merupakan penelitian kualitatif berbasis studi pustaka dengan pendekatan teologis normatif dan korelatif. Analisis dilakukan terhadap pemikiran Zizioulas mengenai komunio dan perikoresis, serta dialognya dengan konsep hospitalitas Kristus dan kepemimpinan melayani dalam konteks tantangan gereja di Indonesia. Hasil pembahasan menunjukkan bahwa eklesiologi komunio menempatkan gereja sebagai persekutuan yang berakar pada relasi Allah Tritunggal, sedangkan perikoresis memperlihatkan pola relasional yang dialogis, partisipatif, dan non-dominatif bagi kehidupan bergereja. Dalam kerangka tersebut, hospitalitas Kristus menjadi jembatan antara identitas liturgis gereja dan praksis sosialnya, sementara kepemimpinan melayani menjadi wujud praksis dari kehidupan komunio. Dalam konteks Indonesia yang ditandai oleh pluralitas agama dan budaya, fragmentasi sosial, serta berbagai tantangan pastoral, model kepemimpinan ini menawarkan arah bagi gereja untuk hadir sebagai komunitas yang menyambut, memulihkan, dan memberdayakan. Dengan demikian, tulisan ini menegaskan bahwa kepemimpinan melayani yang berakar pada eklesiologi komunio dan diperkaya oleh hospitalitas Kristus dapat menjadi kontribusi teologis yang relevan bagi pembaruan gereja di Indonesia.